A teoria integracionista de Marcel Mauss / Marcel Mauss’ integrationist theory - Vianna Lopes, Julio Aurelio (Sociologias, 2021)
Pesquisa teórica que correlaciona, na elaboração intelectual de Marcel Mauss (1872-1950), sua classificação de níveis de integração coletiva, contida na obra inacabada A nação, ao conceito de tríplice obrigação de doações, recebimentos e retribuições de quaisquer bens – especialmente formulado no Ensaio sobre a dádiva (1925) – e à formulação ulterior dos modos de reciprocidade (1931). Tal correlação teórico-metodológica ensejaria tanto sua aplicação específica à tipologia maussiana de sociedades quanto, também, para explicar tendências atuais de reconfiguração coletiva e distintas da integração nacional. ==== Theoretical research that correlates, in line with the elaboration by Marcel Mauss (1872-1950), the concept of three social obligations – of giving, receiving and returning goods – which was elaborated in The Gift (1925), and his hierarchy of levels of collective integration, covered by his unfinished work The Nation that predates The Gift. Such theoretical-methodological correlation would stimulate an approach that comprehends both the Maussian formulation of modes of reciprocity (1931) and its particular application to the typology of societies that adopted it, including explaining current tendencies of collective reconfiguration as a distinct characteristic of national integration.